Effects of Cell Temperature and Reactant Humidification on Anion Exchange Membrane Fuel Cells - Van Men Truong (Materials, 2019)
The performance of an anion exchange membrane fuel cell (AEMFC) under various operating conditions, including cell temperature and humidification of inlet gases, was systematically investigated in this study. The experimental results indicate that the power density of an AEMFC is susceptible to the cell temperature and inlet gas humidification. A high performance AEMFC can be achieved by elevating the cell operating temperature along with the optimization of the gas feed dew points at the anode and cathode. As excess inlet gas humidification at the anode is supplied, the flooding is less severe at a higher cell temperature because the water transport in the gas diffusion substrate by evaporation is more effective upon operation at a higher cell temperature. The cell performance is slightly affected when the humidification at the anode is inadequate, owing to dehydration of the membrane, especially at a higher cell temperature. Furthermore, the cell performance in conditions of under-humidification or over-humidification at the cathode is greatly reduced at the different cell temperatures tested due to the dehydration of the anion exchange membrane and the water shortage or oxygen mass transport limitations, respectively, for the oxygen reduction reaction. In addition, back diffusion could partly support the water demand at the cathode once a water concentration gradient between the anode and cathode is formed. These results, in which sophisticated water management was achieved, can provide useful information regarding the development of high-performance AEMFC systems.